Analisis Hubungan Minat dan Hasil Belajar Fisika Siswa Kelas XI SMA Negeri Terawas - Mohamad Ali; Dodik Mulyono; Sulistiyono (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to determine the relationship between students' learning interest and their physics learning outcomes at SMA Negeri Terawas. The research employed a quantitative method with a descriptive correlational approach. The population consisted of all students of SMA Negeri Terawas, while the sample comprised 68 eleventh-grade students selected as respondents. Data were collected using a questionnaire to measure students' learning interest and documentation of physics learning outcomes. Data analysis was conducted using SPSS through prerequisite tests, including normality and linearity tests, followed by the Pearson correlation test to examine the research hypothesis. The results showed that there was a significant relationship between students' learning interest and their physics learning outcomes at SMA Negeri Terawas. In conclusion, learning interest has a significant relationship with physics learning outcomes, indicating that students with higher learning interest tend to achieve better physics learning outcomes.  Keywords: Physics Learning Outcomes, Learning Interest